Військова політика Республіки Молдова 1991-2011 рр. - Левик, Б. (Схід, 2012)
У статті поданий військово-історичний аналіз передумов створення Збройних сил Молдови, її військової політики в регіоні та на міжнародній арені. Проаналізовані основні державні законодавчі акти, які забезпечують військову безпеку республіки. Охарактеризовано військовий потенціал. Окреслені україно-молдовські відносини. Military and historical analysis behind the background of creating the armed forces of Moldova, its defence policy in the region and international stage has been carried out, as well as examination of the groundlaying legislative acts guaranteeing the security sphere. Military potential of Moldavian armed forces has been evaluated, while bilateral Ukrainian-Moldavian relations have been summarized.